Đặt từng cái căn là a và b, đưa về dạng
\(\left(a-b\right)\left(ab+1\right)=a^2-b^2\)
Chuyển vế đưa về phương trình tích là xong
Đặt từng cái căn là a và b, đưa về dạng
\(\left(a-b\right)\left(ab+1\right)=a^2-b^2\)
Chuyển vế đưa về phương trình tích là xong
giải pt
\(\left(\sqrt{x+5}-\sqrt{x+2}\right)\left(1+\sqrt{x^2+7x+10}\right)=3\)
GPT: \(\left(\sqrt{x+5}-\sqrt{x+2}\right)\left(1+\sqrt{x^2+7x+10}\right)=3\)
Giai phương trình:\(\left(\sqrt{x+5}-\sqrt{x+2}\right)\left(\sqrt{x^2+7x+10}+1\right)=3\)
Giải phương trình :
\(\left(\sqrt{x+5}-\sqrt{x-2}\right)\left(1+\sqrt{x^2+7x+10}\right)=3\)
giải pt: \(\left(\sqrt{x+5}-\sqrt{x+2}\right)\left(1+\sqrt{x^2+7x+10}\right)=3\)
\(\left(\sqrt{x+2}-\sqrt{x-2}\right)\left(1+\sqrt{x^2+7x+10}\right)=3\)
giai phuong trinh
\(\left(\sqrt{x+5}-\sqrt{x+2}\right)\left(1+\sqrt{x^2+7x+10}\right)=3\)
giải pt:
a. \(10.\sqrt{X^3+1}=3\left(X^2+2\right)\)
b. \(\left(\sqrt{X+5}-\sqrt{X+2}\right)\left(1+\sqrt{X^2+7X+10}\right)=3\)
c. \(\sqrt{3X^2-18X+28}+\sqrt{4X^2-24X+45}=-5-X^2+6X\)
d. \(\sqrt{2X-3}+\sqrt{5-2X}=3X^2-12X+14\)
1)\(7\sqrt{3x-7}+\left(4x-7\right)\sqrt{7-x}=32\)
2)\(4x^2-11x+6=\left(x-1\right)\sqrt{2x^2-6x+6}\)
3)\(9+3\sqrt{x\left(3-2x\right)}=7\sqrt{x}+5\sqrt{3-2x}\)
4)\(\sqrt{2x^2+4x+7}=x^4+4x^3+3x^2-2x-7\)
5)\(\frac{6-2x}{\sqrt{5-x}}+\frac{6+2x}{\sqrt{5+x}}=\frac{8}{3}\)
6)\(2\left(5x-3\right)\sqrt{x+1}+\left(x+1\right)\sqrt{3-x}=3\left(5x+1\right)\)
7)\(\sqrt{7x+7}+\sqrt{7x-6}+2\sqrt{49x^2+7x-42}=181-14x\)